Strength Deterioration of Concrete in Sulfate Environment: An Experimental Study and Theoretical Modeling - Yingwu Zhou; Hao Tian; Lili Sui; Feng Xing; Ningxu Han (Advances in Materials Science and Engineering)
Sulfate corrosion is one of the most important factors responsible for the performance degradation of concrete materials. In this paper, an accelerated corrosion by a sulfate solution in a dry-wet cycle was introduced to simulate the external sulfate corrosion environment. The deterioration trend of concrete strength and development law of sulfate-induced concrete corrosion depth under sulfate attacks were experimentally studied. The damaged concrete section is simply but reasonably divided into uncorroded and corroded layers and the two layers can be demarcated by the sulfate corrosion depth of concrete. The accelerated corrosion test results indicated that the strength degradation of concrete by sulfate attack had a significant relation with the corrosion depth. Consequently, this paper aims to reveal such relation and thus model the strength degradation law. A large amount of experimental data has finally verified the validity and applicability of the models, and a theoretical basis is thus provided for the strength degradation prediction and the residual life assessment of in-service concrete structures under sulfate attacks.